Implementasi Peraturan Daerah Provinsi Sumatera Utara Tentang Pengutamaan Bahasa Indonesia dan Perlindungan Bahasa dan Sastra Daerah - Pane, Fatma Sani; Kadir, Abdul; Harahap, Dumasari (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2020)
This study aims: To analyze how the implementation of local regulation No. 8 of 2017 concerning the prioritization of Indonesian language and the protection of regional languages and regional literature in the DPRD Province North Sumatra Secretariat, Analyze the constraints of the implementation of regional regulations No. 8 of 2017 on prioritizing Indonesian and protecting Regional Languages and Regional Literature at the North Sumatra Provincial DPRD Secretariat. This study uses descriptive qualitative method and data collection techniques through observation, interviews and documentation with informants 5 {five} people and literature studies.Based on the results of this study, that there are still many employees who use Regional Languages in the North Sumatra Provincial DPRD Secretariat Office, this is due to a lack of awareness in using Indonesian language that is good and correct in public spaces and official forums. With this outreach, the public and especially employees in the Sumatra Provincial Secretariat know about it and to communicate prioritize Indonesian and when communicating using Regional Languages so that they are preserved only in group communication.